Parameters of passenger facilities according to railway station characteristics - Havlena O.; Jacura M.; Týfa L.; Javořík T.; Svetlík M. (Wydawnictwo Politechniki Śląskiej, 2014)
The article presents ways and goals of railway stations and stops at Czech Railway Network. The aim of this categorisation is to classify railway stations (or stops) at railway network according to suite of entrance parameters (e.g. municipality population, transfer links, job opportunities, touristic attractiveness). On the basis of these parameters, railway stations and stops will be classified to several categories, which will be used to specify the conclusions for station equipment concerning ticket offices, commercial services, waiting rooms and other accessories. Research results can be used as a support for infrastructure managers and railway operators to optimise the scale of their services.
Keywords: railway station; stops; passenger facilities; categorization